Log(f-3)=log(17-4f)

Simple and best practice solution for Log(f-3)=log(17-4f) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Log(f-3)=log(17-4f) equation:


Simplifying
Log(f + -3) = log(17 + -4f)

Reorder the terms:
goL(-3 + f) = log(17 + -4f)
(-3 * goL + f * goL) = log(17 + -4f)

Reorder the terms:
(fgoL + -3goL) = log(17 + -4f)
(fgoL + -3goL) = log(17 + -4f)
fgoL + -3goL = (17 * glo + -4f * glo)

Reorder the terms:
fgoL + -3goL = (-4fglo + 17glo)
fgoL + -3goL = (-4fglo + 17glo)

Solving
fgoL + -3goL = -4fglo + 17glo

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '4fglo' to each side of the equation.
fgoL + 4fglo + -3goL = -4fglo + 4fglo + 17glo

Reorder the terms:
4fglo + fgoL + -3goL = -4fglo + 4fglo + 17glo

Combine like terms: -4fglo + 4fglo = 0
4fglo + fgoL + -3goL = 0 + 17glo
4fglo + fgoL + -3goL = 17glo

Add '3goL' to each side of the equation.
4fglo + fgoL + -3goL + 3goL = 17glo + 3goL

Combine like terms: -3goL + 3goL = 0
4fglo + fgoL + 0 = 17glo + 3goL
4fglo + fgoL = 17glo + 3goL

Reorder the terms:
4fglo + fgoL + -17glo + -3goL = 17glo + -17glo + 3goL + -3goL

Combine like terms: 17glo + -17glo = 0
4fglo + fgoL + -17glo + -3goL = 0 + 3goL + -3goL
4fglo + fgoL + -17glo + -3goL = 3goL + -3goL

Combine like terms: 3goL + -3goL = 0
4fglo + fgoL + -17glo + -3goL = 0

Factor out the Greatest Common Factor (GCF), 'go'.
go(4fl + fL + -17l + -3L) = 0

Subproblem 1

Set the factor 'go' equal to zero and attempt to solve: Simplifying go = 0 Solving go = 0 Move all terms containing f to the left, all other terms to the right. Add '-1go' to each side of the equation. go + -1go = 0 + -1go Remove the zero: 0 = -1go Simplifying 0 = -1go The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(4fl + fL + -17l + -3L)' equal to zero and attempt to solve: Simplifying 4fl + fL + -17l + -3L = 0 Reorder the terms: -3L + fL + 4fl + -17l = 0 Solving -3L + fL + 4fl + -17l = 0 Move all terms containing f to the left, all other terms to the right. Add '3L' to each side of the equation. -3L + fL + 4fl + 3L + -17l = 0 + 3L Reorder the terms: -3L + 3L + fL + 4fl + -17l = 0 + 3L Combine like terms: -3L + 3L = 0 0 + fL + 4fl + -17l = 0 + 3L fL + 4fl + -17l = 0 + 3L Remove the zero: fL + 4fl + -17l = 3L Add '17l' to each side of the equation. fL + 4fl + -17l + 17l = 3L + 17l Combine like terms: -17l + 17l = 0 fL + 4fl + 0 = 3L + 17l fL + 4fl = 3L + 17l The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 17x+3y=45.80 | | 0.2+x=1 | | -4x-16=-5-3x | | X^2+2x+25=9 | | 6y=5x+8 | | 8y-7x+2y-y= | | 5p+6=2p+12 | | 14+n=3n+6 | | m/9*100=140 | | 35=5/7u | | 0.05x-2.5=0.3(x+5) | | m/9.100=140 | | 10x/10=28 | | 8(x+4)=7(x-5)+x | | 7n-4=3n-8 | | V-60=57 | | -16t^2+72t+5=0 | | 9x-y=-6 | | 3(2x+5)+3=36 | | 18x^2+45xy-8y^2=0 | | x^2-x-20=3x+12 | | 3(2x-1)=4x-7 | | y=x(2i*3i) | | 6(x+1)/4=3x-1 | | y=4-4+2y | | 2(x+4)/4=4x-3 | | 4x+20=2x-3 | | 6x+17=-3x+35 | | 4-5n=-9+8n | | V(x)=7/3x | | 12x-4=-16x+8 | | 12x-5x+150=12x+65 |

Equations solver categories